Analisis Kesesuaian Lahan Pertanian dengan Program Lahan Sawah Dilindungi di Kabupaten Lombok Barat - Febrita Susanti; Rasyid Ridha; Baiq Harly Widayanti (Universitas Hamzanwadi, 2023)
Protected paddy fields (LSD) is one of the government programs from the Ministry of Agrarian and Spatial Planning / Head of the National Land Agency which aims to control the conversion of rice fields and meet the availability of paddy fields to support national food. The agriculture office has also developed the concept of sustainable agricultural land and food (LP2B) which will be used as regional regulations that will be a reference in development and have goals that are in line with LSD. The obstacle to the implementation of this government program is land ownership by residents, so it tends to be difficult to maintain agricultural areas, West Lombok Regency based on the decision of the Minister of Agrarian and Spatial Planning / Head of the National Land Agency has determined a map of protected rice fields (LSD) covering an area of 9,102.17 Ha which is currently unknown condition, whether this area has been fulfilled properly. The purpose of this study is to determine the suitability of agricultural land by looking at the protected paddy field program. The research method uses argis overlay analysis and literature studies and interviews. The results of the analysis found that the unsuitable land area was 992.03 ha or 7% of the total area of protected rice fields based on the Regional Spatial Plan (RTRW). The findings were that there were 26501.62 ha of paddy field designation in accordance with the RTRW that had not been designated as protected rice fields (LSD).